Synthesis of Nitrogen- and Oxygen-Containing Heterocycles by Prins Cyclization in Continuous Flow - Talavera-Alemán, Armando; Marrot, Jérome; Dagousset, Guillaume; Thomassigny, Christine (Synthesis, 2020)
Aza-silyl-Prins and oxa-Prins cyclization reactions in continuous-flow chemistry are described for the synthesis of the corresponding tetrahydropyridines and pyran derivatives, respectively. In particular, the use of pyridine-carboxaldehydes for aza-silyl-Prins reaction led to either a symmetrical triarylmethane or two new bicyclic compounds. 4-Fluorinated-2-substituted tetrahydropyran derivatives were also obtained in the oxa-Prins cyclization with good selectivity in favor of the anti-isomer.
Keywords: aza-silyl-Prins; oxa-Prins; continuous-flow chemistry; tetrahydropyridine; dihydropyran